Exploring Nanoscale Lubrication Mechanisms of Multilayer MoS2 During Sliding: The Effect of Humidity - Claerbout, Victor E. P.; Nicolini, Paolo; Polcar, Tomas (Frontiers in Chemistry, 2021)
Solid lubricants have received substantial attention due to their excellent frictional properties. Among others, molybdenum disulfide (MoS 2 ) is one of the most studied. Humidity results in a deterioration of the frictional properties of MoS 2 . The actual mechanism at the nanoscale is still under debate, although there are indications that chemical reactions are not likely to occur in defect-free structures. In this study, we performed non-equilibrium molecular dynamics simulations to study the frictional properties of multilayer MoS 2 during sliding in the presence of water. Moreover, we also investigated the effect of sliding speed and normal load. We confirmed earlier results that a thin layer of water organizes as a solidified, ice-like network of hydrogen bonds, as a result of being confined in a two-dimensional fashion between MoS 2 . Moreover, we found that there exists an energy driven, rotational dependence of the water network atop/beneath MoS 2 . This orientational anisotropy is directly related to the dissipative character of MoS 2 during sliding. Finally, three distinct frictional regimes were identified, two for a thin layer of water and one for bulk water. In the case of a thin layer and low coverage, water represents a solid-like contaminant, causing high energy dissipation. For a thin layer and high coverage, water starts to act as a solid-like lubricant, reducing dissipation during sliding. And finally, a regime where water acts as a liquid lubricant, characterized by a clear velocity dependence.